On the microstructure evolution in tungsten ITER monoblocks: A computational study - Castin, N.; Van den Kerkhof, S.; Bonny, G.; Terentyev, D. (Computational materials science, 2023)
We perform a combined study, coupling three computational methods, to assess the impact of neutron irradiation and temperature transients on the integrity of tungsten monoblocks in the future ITER device. These plasma-facing components will indeed be subject to unsteady heat loads and neutron bombardment, whose combination induces a degradation of the mechanical properties in a heterogeneous manner. Though both phenomena have received substantial attention in literature, their combined effects are not well known. The first tool is an in-house finite volume based solver for the heat conduction equation, which is dedicated to the evaluation of temperature profiles, during steady state and typical transient conditions, such as (mitigated) type I edge localized modes and slow power transients. The second tool is a multiscale object Kinetic Monte Carlo (OKMC) model, dedicated to the prediction of the microstructure evolution under high-energy neutron bombardment, given the local temperature as input. Finally, the last tool estimates the macroscopic properties of the tungsten material, given the microstructure as predicted by the OKMC tool. As a result of the combined study, we find that thermal transients alleviate the degradation of mechanical properties for the most part of the monoblock components, at the exception of the areas close to the cooling pipes where, on the contrary, the degradations kinetics are accelerated.